2023
DOI: 10.3390/pharmaceutics15020323
|View full text |Cite
|
Sign up to set email alerts
|

Inclisiran—Safety and Effectiveness of Small Interfering RNA in Inhibition of PCSK-9

Abstract: Dyslipidemia is listed among important cardiovascular disease risk factors. Treating lipid disorders is difficult, and achieving desirable levels of LDL-cholesterol (LDL-C) is essential in both the secondary and primary prevention of cardiovascular disease. For many years, statins became the basis of lipid-lowering therapy. Nevertheless, these drugs are often insufficient due to their side effects and restrictive criteria for achieving the recommended LDL-C values. Even the addition of other drugs, i.e., ezeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 112 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…The safety, tolerability, and efficacy of inclisiran have been studied within the ORION clinical development program who demonstrated a sustained PCSK9 suppression of about 80% and time-adjusted LDL-C reduction of approximately 50% from baseline. Furthermore, the safety profile of inclisiran was found to be comparable to that of mAb PCSK9i and the most commonly reported adverse effect was a mild-to-moderate transient injection site reaction [3]. It provides a therapeutic opportunity to overcome drugs intolerance and decrease the burden of atherosclerotic cardiovascular disease.…”
Section: Inclisiran and Lipoprotein Apheresis In Statin Intolerance H...mentioning
confidence: 88%
See 1 more Smart Citation
“…The safety, tolerability, and efficacy of inclisiran have been studied within the ORION clinical development program who demonstrated a sustained PCSK9 suppression of about 80% and time-adjusted LDL-C reduction of approximately 50% from baseline. Furthermore, the safety profile of inclisiran was found to be comparable to that of mAb PCSK9i and the most commonly reported adverse effect was a mild-to-moderate transient injection site reaction [3]. It provides a therapeutic opportunity to overcome drugs intolerance and decrease the burden of atherosclerotic cardiovascular disease.…”
Section: Inclisiran and Lipoprotein Apheresis In Statin Intolerance H...mentioning
confidence: 88%
“…Inclisiran is a novel small interfering RNA-based drug (siRNA) anti-PCSK9 play a role in patients when optimal LDL-C cannot be achieved by statins and/or mAb PCSK9i [3].…”
Section: Inclisiran and Lipoprotein Apheresis In Statin Intolerance H...mentioning
confidence: 99%
“…Primenjuje se kao supkutana injekcija u dozi od 284 mg. Posle inicijalne primene leka, druga doza se dobija nakon tri meseca, a svaka sledeća na 6 meseci 29 . Glavna prednost inklisirana u odnosu na PCSK9 monoklonska antitela je režim doziranja i dugotrajniji efekat koji obezbeđuje bolju komplijansu 30 .…”
Section: Inklisiranunclassified
“…44,45 Treatment with a PCSK9i is associated with reductions in triglycerides (TGs), VLDL cholesterol (VLDL-C) and VLDL remnants, intermediate-density lipoprotein cholesterol (IDL-C), non-high-density lipoprotein cholesterol (non-HDL-C), apoB and lipoprotein(a) (Lp[a]). 17,18,41,43,[46][47][48] Non-HDL-C (containing VLDL, IDL, LDL, chylomicron remnants, and Lp[a]) is advantageous over LDL-C since it is not influenced by TG variability and contains lipoprotein with remnant cholesterol. 35,41 The administration of PCSK9i also increases apolipoprotein A-I (apoA-I) and HDL-C. 41…”
Section: Effect Of Psck9i On Lipid Parametersmentioning
confidence: 99%
“…35,53 Inclisiran reduces both the intracellular and extracellular levels of PCSK9, unlike mAbs which only influence the extracellular PCSK9 levels. 46 The clinical efficacy and safety of inclisiran in lowering LDL-C have been explored in randomized, placebo-controlled, double-blind clinical trials. 54,55 ORION-9, ORION-10, and ORION-11 phase 3 trials have demonstrated that the inclisiran regimen of 284 mg (equivalent to 300 mg inclisiran sodium) has good efficacy for LDL-C level reduction.…”
Section: Inclisiranmentioning
confidence: 99%